Fast-velocity Resistance Training Improves Force Development and Mobility in Multiple Sclerosis - Andreu-Caravaca, Luis; Ramos-Campo, Domingo Jesús; Chung, Linda H.; Manonelles, Pedro; Boas, Joao Paulo Vilas; Rubio-Arias, Jacobo Ángel (International Journal of Sports Medicine, 2022)
This study aimed to analyze the benefits of a lower-limb fast-velocity concentric resistance training on rate of force development, mobility, and quality of life in people with Multiple Sclerosis. A randomized controlled trial was conducted in 30 people with Multiple Sclerosis, who were randomly assigned to either an experimental (n=18) or a control (n=12) group. The experimental group carried out 10-weeks of fast-velocity concentric resistance training, while the control group did not perform any intervention. Early and late rate of force development during knee extension in both legs, sit-to-stand and Timed Up and Go tests and quality life questionnaire were evaluated before and after intervention. The training program evoked an increase in early rate of force development in experimental group (0–30; Rightleg: 63.9%, p<0.001; ES=-1.4; Leftleg: 52.7%, p<0.001; ES=-1.0) compared to control group (showed modest increases). Furthermore, experimental group improved mobility after training (Sit-to-stand: 22.2%, p<0.001; ES=1.0; Timed Up and Go Test: 10.1%, p<0.001; ES=1.1) and increased the perception of quality of life after training, while control showed no changes. The fast-velocity concentric resistance training has the potential to improve early rate of force development and mobility after 10-weeks of training. In addition, the increase in self-perceived quality of life following this training modality demonstrates promising results in the Multiple Sclerosis population.
Keywords: neurodegenerative disorders; exercise; strength; neuromuscular